2015
DOI: 10.1038/npp.2015.170
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphism of the FKBP5 Gene and Childhood Maltreatment as Predictors of Structural Changes in Brain Areas Involved in Emotional Processing in Depression

Abstract: The gene expressing the FK506 binding protein 51 (FKBP5) is involved in the regulation of glucocorticoid receptor sensitivity. The rs1360780 SNP in this gene (T allele vs C homozygous) has been found to be associated with major depressive disorder (MDD). The aim of our study was to investigate whether this polymorphism might be associated with altered brain structure and function in a cohort of 40 patients with MDD and 43 healthy controls. A functional magnetic resonance imaging (fMRI) emotional attention task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 50 publications
3
52
0
1
Order By: Relevance
“…Our finding, however, was that of gene-environment interaction, and thus adds to the growing literature supporting the role of FKBP5 in susceptibility to maltreatment and childhood trauma. While most studies implicating FKBP5 in vulnerability to maltreatment were conducted in adults (Bevilacqua et al, 2012;Fani et al, 2014;Buchmann et al, 2014;Tozzi et al, 2015), the present study suggests that this susceptibility may emerge early in life. The FKBP5 gene is differentially methylated in maltreated as opposed to non-maltreated children (Weder et al, 2014), this methylation is allele-specific (Klengel et al, 2013) which suggests that the underlying mechanism of this gene-environment interaction is epigenetic.…”
Section: Discussionmentioning
confidence: 60%
“…Our finding, however, was that of gene-environment interaction, and thus adds to the growing literature supporting the role of FKBP5 in susceptibility to maltreatment and childhood trauma. While most studies implicating FKBP5 in vulnerability to maltreatment were conducted in adults (Bevilacqua et al, 2012;Fani et al, 2014;Buchmann et al, 2014;Tozzi et al, 2015), the present study suggests that this susceptibility may emerge early in life. The FKBP5 gene is differentially methylated in maltreated as opposed to non-maltreated children (Weder et al, 2014), this methylation is allele-specific (Klengel et al, 2013) which suggests that the underlying mechanism of this gene-environment interaction is epigenetic.…”
Section: Discussionmentioning
confidence: 60%
“…In this systematic review, neuroimaging alteration in MDD was found to be associated with FK506‐binding protein 51 (FKBP5) and corticotropin‐releasing hormone receptor 1 (CRHR1) genes . The dysfunction of glucocorticoid receptor and endogenous glucocorticoid levels impair the HPA axis feedback inhibition in depressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…70,71 MDD patients with an MAOA H-allele showed significantly lower amygdalaprefrontal connectivity, 72 but not in those with 5-HTTLPR genetic variants. 70,73 Other studies have reported significant genotype-diagnosis interaction effects on emotional regulation systems for FKBP5, 74 CACNA1C, 75 CRHR1, 64 and BICCI 39 genes. The remaining studies showed decreased activation of the striatum with a PCLO risk allele, decreased activation of right frontal middle gyrus in a 5-HT2A T-allele, or decreased connectivity of amygdala-prefrontal circuitry with the MAOA H-allele.…”
Section: Genetic-neuroimaging Association Using Task-fmrimentioning
confidence: 98%
See 1 more Smart Citation
“…Initial studies that combined a candidate gene approach with neuroimaging reported that specific single-nucleotide polymorphisms (SNPs) of genes associated with neuroplasticity and stress reactivity, including brain derived neurotrophic factor, glucocorticoid and oxytocin receptor sensitivity, confer greater sensitivity to the detrimental impact of ELS, e.g. pronounced reductions of limbic volumes (Dannlowski et al 2016;Tozzi et al 2016;van Velzen et al 2016). Interestingly, two initial studies reported that specific allelic combinations associated with differences in central dopamine and serotonergic functioning exhibited ELS-associated changes in hippocampal and amygdala activation that may reflect improved threat learning and implicit emotion regulation following early aversive experiences (Hermann et al 2012;van Rooij et al 2017).…”
Section: Introductionmentioning
confidence: 99%